VLSI implementation of controllers for communication protocols fromtheir Petri net models - Khan, A.M.T. (1992)
Petri nets are popular in the communication protocol community for modelling and analysis purposes. This paper gives a procedure for extraction and implementation of controllers of protocols from their Petri net model. It adds another dimension to the use of Petri nets and is suited for network, transport and data link protocols